1996
DOI: 10.1074/jbc.271.43.26561
|View full text |Cite
|
Sign up to set email alerts
|

Gq-coupled Receptors Transmit the Signal for GLUT4 Translocation via an Insulin-independent Pathway

Abstract: Guanosine 5-O-(3-thiotriphosphate) (GTP␥S) induces the translocation of glucose transporter type 4 (GLUT4) from an intracellular pool to the cell surface and increases glucose uptake in adipocytes. The GTP-binding protein(s) responsible for the translocation has remained to be identified. Using a sensitive and quantitative method to assess the translocation of c-MYC epitope-tagged GLUT4, we obtained evidence that the activation of receptor-coupled G q (neither G i nor G s ) triggered GLUT4 translocation in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 64 publications
2
39
0
Order By: Relevance
“…4A). We previously developed a sensitive and quantitative method to measure GLUT4 translocation by detecting C-Myc epitope-tagged GLUT4 (GLUT4myc), which is exogenously expressed on the cell surface (23,(33)(34)(35)(36). Using this system, we found that insulin-stimulated GLUT4 translocation was not altered by transient expression of APS wild-type or Y618F mutant in 3T3L1-G4myc-CAR⌬1 adipocytes (Fig.…”
Section: Diabetes Vol 52 November 2003mentioning
confidence: 99%
“…4A). We previously developed a sensitive and quantitative method to measure GLUT4 translocation by detecting C-Myc epitope-tagged GLUT4 (GLUT4myc), which is exogenously expressed on the cell surface (23,(33)(34)(35)(36). Using this system, we found that insulin-stimulated GLUT4 translocation was not altered by transient expression of APS wild-type or Y618F mutant in 3T3L1-G4myc-CAR⌬1 adipocytes (Fig.…”
Section: Diabetes Vol 52 November 2003mentioning
confidence: 99%
“…These treatments can result in increased AMP levels, and it has been suggested that activation of the AMPdependent protein kinase stimulates glucose uptake (29). G protein-coupled receptors linked to G q have also been observed to induce GLUT4 translocation (30). Future studies will be necessary to ascertain the specific roles and relationships between protein kinase B, protein kinase C and , and/or other PI 3-kinase-dependent as well as independent signaling processes in GLUT4 translocation.…”
Section: Insulin Regulation Of Glucose Uptakementioning
confidence: 99%
“…in a previous study we reported that activation of gαq protein-coupled receptors (gαqPcrs), such as the α1b adrenergic receptor (α1bar) or b2 bradykinin receptor (bK 2 r), also triggered gLuT4 translocation and stimulated glucose uptake in cultured cells [30,31]. gLuT4 translocation and glucose uptake induced by gαqPcr activation is physiologically important in muscles and adipocytes [32][33][34][35].…”
Section: Materials and Antibodiesmentioning
confidence: 99%
“…chO-gLuT4myc cells stably expressing the human α1b-adrenergic receptors and the human bradykinin B 2 receptors, were called chO-gLuT4myc-α1bar cells and chO-gLuT4myc-bK 2 r cells respectively and were as previously described [30,31]. L6-gLuT4myc cells were L6 cells stably expressing gLuT4myc and L6-gLuT4myc-bK 2 r cells were L6-gLuT4myc cells stably expressing the mouse bradykinin b 2 receptors, as previously described [31].…”
Section: Stable Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation